Enhancing accountability through web based disclosure practices of foundations in Malaysia - Iffah Ghazali, Nurul; Afiqah Md Amin, Nur; Fadhilah , Rina (Edelweiss Applied Science and Technology, 2024)
The accountability of non-profit organizations (NPOs) in managing public funding is at risk due to numerous cases reported on the misappropriation of funds and falsifying the reporting information of NPOs. Often, NPOs have been criticized as less efficient and transparent in managing public funds for targeted beneficiaries. As the public trust is deteriorating, alternative reporting could be pertinent to enhance transparency and accountability of NPOs towards stakeholders and the public at large. Therefore, this paper aims to analyse the extent of disclosure among 122 foundations in Selangor and Kuala Lumpur through web-based reporting. This paper used a content analysis approach to gather information in relation to web-based reporting adapted from the Web-based Accountability Index from Gandini et. al (2012) and Nair et. al (2022). The findings indicated the foundations in Malaysia show an average of accountability discharged through websites’ reporting. The foundations were also unlikely to publish financial information and social reporting as compared to other general information. The findings also suggested NPO communities the significant use of web-based technologies as a mechanism to gain and sustain stakeholders’ trust and confidence towards public funds’ accountability.